One new species of the genus Acosmetura (Orthoptera: Tettigoniidae: Meconematinae) from Sichuan with description of the female of Xiphidiopsis (Euxiphidiopsis) spicula Su, An & Shi, 2023 - Su, Jie; Wang, Tingting; Shi, Fuming (Zootaxa, 2025)
This paper reports one new species of the genus Acosmetura Liu, 2000, i.e. Acosmetura mecyna sp. nov., and presents the initial description of the female of Xiphidiopsis (Euxiphidiopsis) spicula Su, An & Shi, 2023. Diagnostic illustrations are provided, and all specimens examined are deposited in the Museum of Hebei University, China.